Willingness to communicate, interest, motives to communicate with the instructor, and L2 speaking: a focus on the role of age and gender. Issue 3 (3rd July 2018) - Amiryousefi, Mohammad
ABSTRACT: This study investigated how well interest and motives to communicate with the instructor (MCI) predict L2 willingness to communicate (WTC) and L2 speaking among English as a foreign language (EFL) learners, and tested whether these variables predict L2 WTC and speaking differently across different age and sex groups. It also examined whether there are meaningful differences between EFL learners who have a higher level and those who have a lower level of L2 speaking in terms of L2 WTC, interest, and MCI and between male and female learners in their motives to communicate with their English instructors. Some 612 pre-intermediate EFL learners participated in the study. A quantitative method using questionnaires was used to collect the data. The results revealed that (1) interest and MCI made significant contributions to the participants' L2 WTC and speaking; (2) the variables predicted L2 WTC and speaking differently across different age and sex groups; (3) there were significant differences between the learners in the high L2 speaking group and those in the low L2 speaking group in terms of WTC, interest, and MCI; and (4) male participants reported communicating with their teachers more for the participatory and sycophantic motives than female learners.